A Case Study On The Representation Of Chinese Characters In 29 Februari And Ola Bola - Beh, Kay Hien (2021)
This research aimed to achieve two key objectives: 1) Select and review two Malaysian films, and 2) Study the Chinese characters found in the two chosen Malaysian films. A qualitative research using textual analysis was used to read text from the two chosen films which were 29 Februari and Ola Bola. The Constructivist Discourse Analysis view was adopted with Stuart Hall’s approach towards media representation serving as a guide to read film text. Hall affirmed that there are no true fixed meaning to a message as representations are constitutive of an event and can change according to its form. Mise-en-scene was deployed to collect, analyse, and interpret data from the chosen films. The research focused on the main and selected Chinese characters of the chosen films. These characters were analysed to identify any assigned stereotypes or themes in the chosen films. Several themes were found ranging from the portrayal of wealth disparity among Chinese characters, a focus on a patriarchal Chinese society, Chinese’s ability to speak other languages, and also being Chinese portrayed as comedic relief characters. This research further substantiated existing arguments by other researchers that Chinese characters in Malaysian films are subjected to stereotypical portrayals in films. Moreover, interracial differences were used to create conflict in the chosen films. That said, ii the representation of Chinese characters in the chosen films suggests the filmmaker’s willingness to acknowledge these stereotypes and using them to create future discussions on these stereotypes as the Chinese characters in both films, while being subjected to stereotypical portrays, did end up with positive character growth in the chosen films. Beyond the analysis of Chinese characters, future research should focus on other races in Malaysia in order to provide a holistic view towards the representation of characters in Malaysian films.